Assessing Institutional Resilience Index of Surabaya City Against Earthquake Risk: A Case Study Using the CDRI Framework - Farah Sabara Putri Puspita; Adjie Pamungkas (Jurnal Penataan Ruang, 2025)
Urban areas in Indonesia are increasingly exposed to seismic risk due to rapid urbanization and limited disaster risk reduction (DRR) integration in spatial planning. This study aims to reassess the institutional resilience of Surabaya City to earthquake disasters using the Climate and Disaster Resilience Initiative (CDRI) framework. A mixed-method approach was employed, combining stakeholder-based surveys and in-depth interviews with representatives from government, academia, civil society, and the private sector. The assessment covered five institutional indicators: DRR mainstreaming, crisis management effectiveness, knowledge dissemination, multi-actor cooperation, and governance. The results show that while Surabaya has demonstrated improvements in technical capacity, public outreach, and emergency response readiness, significant weaknesses remain in strategic planning, inter-agency coordination, and the use of localized hazard data. The city lacks a comprehensive disaster management plan, a functional early warning system, and fully operational contingency frameworks. Despite these limitations, Surabaya excels in emergency communication, community-based awareness programs, and operational response through units such as Command Center 112 and TRC Petir. The overall institutional resilience index indicates moderate progress, with urgent needs for data-based planning, inclusive collaboration, and capacity-building at the local level. These findings highlight the importance of embedding DRR into long-term urban governance and the need for anticipatory and participatory resilience strategies tailored to the city’s seismic risk context.